Determinant Analysis of the Value of LQ45 Index Companies Listed on the Indonesian Stock Exchange - Rina Tjandrakirana DP; Ermadiani; Abukosim (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to test and find empirical evidence regarding the influence of enterprise risk management (ERM) disclosure, company size, profitability, and leverage on company value. The type of data used is secondary data in the form of company annual reports on companies listed on the Indonesia Stock Exchange. The population in this study is the LQ45 index companies for 2020-2022, and the sampling technique used is the purposive sampling method. In this study there are four independent variables and one dependent variable. The dependent variable in this research is company value, while the independent variable consists of four variables, namely Enterprise Risk Management (ERM) disclosure, company size, Profitability, and Leverage. The analysis technique used is classical assumption testing consisting of a normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test as well as hypothesis testing including multiple linear regression, individual parameter significant test (t-test), simultaneous significant test (F test) and coefficient of determination. The results of this research analysis state that Enterprise Risk Management disclosure has a negative and insignificant effect on company value, and company size has a negative and significant effect on company value. Meanwhile, Profitability and Leverage have a positive and significant effect on company value.